Penggunaan Bahasa Indonesia Sebagai Sarana Peningkatan Citra Profesional dan Keterampilan Berbahasa Bagi Pegawai Kantor - Ariya, Muhammad Daffa; Hafid, Muhammad; Ridhorrahman, Muhammad Irham; Ramadhani, Nadine Chelsea; Ridwan, Naufal Muhamad; Hasnarifa, Naura Shabira; Rizkyanfi, Mochamad Whilky (Lembaga Intelektual Muda (LIM) Maluku, 2025)
This research aims to examine the role of the Indonesian language as a means of enhancing professional image and language skills for office employees. The method used is library research, referring to various written sources such as scientific journals, books, and relevant literature. The data obtained is analyzed interpretatively to understand the role of using good and correct language in improving the effectiveness of communication and office administrative efficiency. The findings indicate that effective use of the Indonesian language can strengthen employees' professional image, increase trust from colleagues and superiors, and create more efficient and productive communication in the office environment. Furthermore, good language skills greatly influence how others perceive an individual’s competence and the credibility of the institution. Therefore, proper language use and strong communication skills play a crucial role in supporting professionalism and employee performance.